A rare case of an antenatally diagnosed tumor of the neck: a hamartoma of the thyroid gland - Zachariou, Zacharias; Beiler, Hans Albert; Roth, Helga; Daum, Roland (Journal of pediatric surgery, 1996)
A case of connatal hamartoma of the left thyroid lobe is reported. During routine prenatal ultrasonographic examination, a tumor of the neck was diagnosed. The baby was born at 30 weeks' gestation, and the tumor (measuring 7.0 × 5.5 × 4.2 cm) was extirpated. Histologically, the tumor was a hamartoma of the thyroid gland. Follow-up evaluation (3 and 6 months after resection) showed that the child was doing well and had no signs of hypothyroidism or hypoparathyroidism. The case is discussed with respect to antenatal diagnosis, postpartum diagnostic measures, management, and surgical therapy.
Elektronische Reproduktion der Druck-Ausgabe 22. Juni 2004
Gesehen am 09.09.2024